2022
DOI: 10.1002/nbm.4877
|View full text |Cite
|
Sign up to set email alerts
|

In vivo phosphorus magnetic resonance spectroscopic imaging of the whole human liver at 7 T using a phosphorus whole‐body transmit coil and 16‐channel receive array: Repeatability and effects of principal component analysis‐based denoising

Abstract: Quantitative three‐dimensional (3D) imaging of phosphorus (31P) metabolites is potentially a promising technique with which to assess the progression of liver disease and monitor therapy response. However, 31P magnetic resonance spectroscopy has a low sensitivity and commonly used 31P surface coils do not provide full coverage of the liver. This study aimed to overcome these limitations by using a 31P whole‐body transmit coil in combination with a 16‐channel 31P receive array at 7 T. Using this setup, we deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(26 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…3). 51 Future development of motion correction techniques is expected to improve spectral quality in the presence of (respiratory) motion, such as for pancreatic tumors, and to reduce signal ghosting from tissues outside the regions of interest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3). 51 Future development of motion correction techniques is expected to improve spectral quality in the presence of (respiratory) motion, such as for pancreatic tumors, and to reduce signal ghosting from tissues outside the regions of interest.…”
Section: Discussionmentioning
confidence: 99%
“…Peak annotations: phosphoethanolamine (PE), phosphocholine (PC), inorganic phosphate (Pi), glycerophosphoethanolamine (GPE), glycerophosphocholine (GPC), phosphatidylcholine (PtdC), α‐, β‐, and γ‐adenosine triphosphate (ATP), nicotinamide adenine dinucleotide (NADH), and uridine diphosphate glucose (UDPG). Source : Adapted from reference 51 . …”
Section: Discussionmentioning
confidence: 99%
“…26 31 P MRS of liver tumors has been performed at magnetic field strengths of 1.5 and 3 T and, because of the low intrinsic sensitivity of 31 P MRS, rather large voxel sizes have been used (up to 560 mL). Moreover, most studies made use of 31 P radiofrequency (RF) transmit-receive surface coils, which have a limited penetration depth and with which therefore metastases may be missed. In a recent study, we have shown that using a 31 P whole-body transmit coil [27][28][29] in combination with a 16-channel receive array 30 at 7 T, it was feasible to acquire 31 P MRSI data with a nominal voxel size of 8 mL and full liver coverage, yielding insight into spatial variations of 31 P metabolites within the healthy liver.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, most studies made use of 31 P radiofrequency (RF) transmit-receive surface coils, which have a limited penetration depth and with which therefore metastases may be missed. In a recent study, we have shown that using a 31 P whole-body transmit coil [27][28][29] in combination with a 16-channel receive array 30 at 7 T, it was feasible to acquire 31 P MRSI data with a nominal voxel size of 8 mL and full liver coverage, yielding insight into spatial variations of 31 P metabolites within the healthy liver. 31 In addition to the sensitivity gain at 7 T, 32,33 the spectral resolution is also enhanced in comparison with lower field strengths, allowing separate detection of the individual PMEs (phosphocholine [PC] and phosphoethanolamine [PE]) and PDEs (glycerophosphocholine [GPC] and glycerophosphoethanolamine [GPE]), 34,35 which may provide even more sensitive and/or specific markers of tumor treatment response.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation